Socio-Economic Life and Institutions in the Traditional Society of Kerala in 18th and 19th Centuries - C.M.Biju, Dr. C.Amirtha Jothi
The society of Kerala in the 18 and 19 centuries was traditional in nature. There were peculiar customs and practices, which separated the society of Kerala from the rest of India. The Marumakkattayam or Matriarchal system of inheritance, the complex and rigid caste system, the residence in a common joint family etc. were some of the peculiar practices in th e traditional society of Kerala. The features of a feudal society and the strong foundation of a caste-dominated society differs Kerala from other parts of the world.